Program Unggulan Tahfiizh: Implementasinya dalam Perkembangan Kognitif Anak - Saniyah, Dyah MInahus; Farhisiyati, Rufa Hindun (Journal of Elementary Education Research, 2024)
This study aims to examine the implementation and outcomes of the Tahfiizh Program in enhancing cognitive abilities and religious values among children at MI Terpadu Al Madani. Using a qualitative approach, data were collected through interviews (with school principals, Tahfiizh mentors, and students), observation, and documentation. Key findings include: (1) The program’s implementation involves three stages: a) Preparation by the principal and formation of a mentoring team; b) Execution through stimulating problem-solving and creative thinking during Quranic memorization; c) Evaluation, which demonstrated increased student motivation and academic achievement. (2) The program successfully improved children’s cognitive functions (memory, problem-solving, creativity) and fostered early attachment to the Quran. Interviews confirmed significant cognitive enhancement post-program. In conclusion, the Tahfiizh Program not only supports intellectual development but also strengthens religious values through a structured and holistic approach, aligning academic and spiritual growth.